Posttraumatic stress disorder and art group therapy: self-expression of traumatic inner world of war veterans - Mandić Gajić, Gordana; Špirić, Željko (Vojnosanitetski pregled, 2017)
Background/Aim. Art therapy and drawings may serve as alternative means of expression and release from trauma among veterans diagnosed with posttraumatic stress disorder (PTSD). Methods. The retrospective clinical study of drawings of war veterans was performed. A total of 89 war veterans met the Diagnostics and Statistical Manual of Mental Disorders (DSM-IV) PTSD criteria and were consecutively admitted to the Day Hospital during 5 years. Art group therapy as part of integrative treatment was performed once a week. The group was open and heterogeneous. Qualitative analysis of drawings content and group protocols were obtained. The drawings were made by free associations. War related themes were explored and descriptive statistics were applied. Results. The most frequent type of common themes of combat stress presented battle and witnessing wounded and killed combatants. Less frequent were themes of graves, destroyed cities and broken trees. The veterans preferred black and red colors with association to death, blood, wounds and destroyed objects. Conclusion. Drawing could provide a unique, complex, visual illustration of war traumatic experiences and memories of posttraumatic stress disorder veterans. Art group discussion might enhance war veterans’ verbal expression due to group support in safe setting. As adjuvant psychotherapy, art group therapy could enrich awareness and the ability of clinicians to treat hard posttraumatic stress disorder symptoms related to uncovered war trauma.
Keywords: stress disorders; post-traumatic; art therapy; veterans; psychotherapy; group; drawings